Bitlis Turizm Araştırmaları - Adıgüzel, Fatih; Uzun, S. Murat; Siyavuş, A. Emrah; Köseoğlu, Abdullah; Korkmaz, Özge; Güleryüz, Umut; Şahinalp, Mehmet Sait; Bozkoyun, Mehmet; Aydın, Şule; Yayla, Eda; Boyunduruk, Adnan; Sönmez, Mehmet Emin; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-